ANALISIS KATA SIFAT DARI PARTIZIPIEN DALAM ROMAN „SOWIESO UND ÜBERHAUPT“ KARYA CHRISTINE NÖSTLINGER - Novilia Putri Dwi Ikhwaningdyah; Putrasulung Baginda; Amir Amir (Allemania, 2023)
In literary texts, various elements contribute to a writer's ability to convey a specific message or describe a particular situation. One such element is the use of adjectives, and this research focuses specifically on adjectives formed from participles, diverging from the commonplace adjectives encountered in everyday language. To facilitate this investigation, the novel "Sowieso und Überhaupt" by Christine Nöstlinger is employed as a primary source due to its rich utilization of participial adjectives. The primary objectives of this research are twofold: (1) to discern the forms of participial adjectives, determining whether they are inflected or not, and (2) to analyze the functions of these adjectives within sentences, shedding light on their attributive, applicative, or predicative roles. By accomplishing these goals, this research aims to enhance our comprehension of the nuanced meanings conveyed by participial adjectives in literary texts. This study adopts a descriptive qualitative approach, initially classifying the gathered data into inflected and non-inflected categories. The analysis reveals that while some participial adjectives exhibit inflection, others can be employed without it, similar to standard adjectives. Consequently, this research yields two recommendations: first, a call to explore the functions of participial adjectives to deepen our understanding of their meanings, and second, an encouragement for further investigation into the variations of verbs influenced by adjectives with applicative functions.